Analisis Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan Cabang Meulaboh dalam Meningkatkan Kepesertaan Pekerja Sektor Informal (BPU) di Kota Meulaboh - Claudia, Vista; Syahril, Syahril (Medan Resource Center, 2024)
The Employment Social Security Organizing Agency (BPJS Ketenagakerjaan) is a legal institution that provides social security to workers who have fixed wages, and also provides assistance to non-wage workers such as fishermen, laborers, and even traders. One of the BPJS Employment branches that provides protection for the informal sector is the Meulaboh BPJS Employment Branch. This is important because in Meulaboh, many people work in the informal sector. The purpose of this research is to analyze how the Meulaboh BPJS Ketenagakerjaan Branch works to increase the number of workers in the informal sector in Meulaboh City, West Aceh. This research uses a qualitative method that describes and explains the situation based on the object of research analyzed by checking the truth of the information obtained from the field. The data used is primary data, which is collected through interviews, observation, and documentation. The results showed that the participation of non-wage workers in the BPJS Ketenagakerjaan program is still low in the informal sector, and many are not registered. This is a problem because in West Aceh there are more workers in the informal sector compared to the formal sector. The lack of protection from labor social security causes unprotected informal workers to immediately get protection from BPJS Employment.